Storytelling as Social Reflection and Pedagogy in Bessie Head’s The Collector of Treasures: Social Reflection and Educational Functions of Storytelling - Megbowon, Funmilola (Journal of Language and Literature Studies, 2026)
Oral tradition such as folklore that include storytelling has historically functioned as a dynamic medium for education, social commentary, social reflection in African societies. This tradition is observed to have been adopted in contemporary African literary writers. While acknowledging that not all African literature uniformly engages with oral tradition in didactic ways, this research examines the extent to which Head’s story The Collector of Treasures acts as a vehicle for social critique and educational enlightenment. Thus, the specific objectives of this study are: i) explore how storytelling functions as a vehicle for social reflection by identifying and critically examining the social issues reflected on in the text; and ii) examine the pedagogical value storytelling provides amidst modern education by analysing the educational insights conveyed through storytelling in the text. The study adopts a qualitative research approach and applies the thematic and interpretive analytical technique. Findings from the analysis show that Head’s story provides reflection on social issues specifically gender-based violence, reproductive coercion, the collapse of family structure and the moral failure of formal education and institutional authorities within the postcolonial contexts. It prompts call for critical reflection on whether traditional and existing social practices, personal behaviour, and societal norms promote values such as responsibility, equity, compassion, justice, and recognises the invaluable role of women. Furthermore, the text educates on the emotional and social consequences of abuse, the value of women’s empowerment through work and education, the importance of love and mutual respect in in human relationships and responsibility. This study concludes that Bessie head effectively adapts the communal, reflective, and instructive functions of oral storytelling to the written form. The study recommends integration of such literary texts in formal educational framework, re-evaluation of the purpose of formal education, and support for women economic empowerment.